Penerapan Model Pembelajaran Scramble Game untuk Meningkatkan Penguasaan Kosakata Pada Pembelajaran Bahasa Indonesia Kelas 1 SD Negeri Minasa Upa Makassar - Rahmawati. A; Abd. Rahman Rahim; Rarman A. Arif (Pusat Riset dan Inovasi Nasional, 2023)
This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is held in two meetings. The research procedure includes planning, implementing actions, observing and reflecting. The subjects of this study were 28 students of grade I at SD Negeri Minasa Upa Makassar. The results of the study showed that the test results for the first cycle of the class average reached 65 with a percentage of 60.7 achieved completeness, with 11 students having achieved mastery and 17 other students not. In cycle II the average obtained was 89.2 with a completeness percentage of 89.3 with 25 students having achieved mastery and 3 people had not. Based on the results of the research above, it can be concluded that the application of the Scramble Game Learning Model can improve vocabulary mastery in Indonesian Language learning Class 1 SD Negeri Minasa Upa Makassar.